Piecing the Broken Golden Bowl: Dislocation and Diplomacy in Nixon in China by John Adams and Alice Goodman - Mathieu Duplay (Transatlantica)
The purpose of this article is to examine the role of line breaks in the libretto Alice Goodman wrote for Nixon in China (1987), her first collaboration with composer John Adams. In the opera, enjambments function first and foremost as literary devices; as such, they emphasize the text’s autonomy and its independence from its musical setting. On a meta-operatic level, the resulting discrepancy between words and music draws attention to the various modes of dislocation at play in an opera whose plot hinges on the acceptance of irreconcilable differences. Finally, the article considers the musical function of line breaks: they loosen up the meter and create complex patterns, which the composer uses for his own purposes.